From the kitchen to the table: southern Illyrian pottery production in the Adriatico-Ionian commerce (1st–3rd century AD) - Shehi, Eduard (Rei Cretariae Romanae Fautorum Acta, 2022)
The study on the pottery discovered recently at the southern Illyrian sites, has given new informations on the local production of several categories, like cooking ware, fine ware, table ware, relief decorated bowls and others. The purpose of this presentation will be to take into account all of them and try to understand their position within the large economic relationship in the Adriatico-Ionian region. Knowing that several local products from this region have been exported to the four directions, it will be interesting to understand why and how different categories of production have ben accepted and preferred within Illyrian and non-Illyrian communities.